2013
DOI: 10.1002/jgra.50169
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric atomic oxygen density estimates using the EISCAT Svalbard Radar

Abstract: [1] Coupling between the ionized and neutral atmosphere through particle collisions allows an indirect study of the neutral atmosphere through measurements of ionospheric plasma parameters. We estimate the neutral density of the upper thermosphere above~250 km with the European Incoherent Scatter Svalbard Radar (ESR) using the year-long operations of the International Polar Year from March 2007 to February 2008. The simplified momentum equation for atomic oxygen ions is used for field-aligned motion in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…We also draw attention to a correction which has been made to the CHAMP measurement shown for pass 9. An earlier figure of 11.09 × 10 13 m −3 was published in the IPY study of Vickers et al [] and corresponded to the only case (pass 4) where the CHAMP measurement did not fall within the error bars of the ESR estimate. However, we have since identified that this measurement corresponded to an incorrect time.…”
Section: Analysis and Resultsmentioning
confidence: 82%
“…We also draw attention to a correction which has been made to the CHAMP measurement shown for pass 9. An earlier figure of 11.09 × 10 13 m −3 was published in the IPY study of Vickers et al [] and corresponded to the only case (pass 4) where the CHAMP measurement did not fall within the error bars of the ESR estimate. However, we have since identified that this measurement corresponded to an incorrect time.…”
Section: Analysis and Resultsmentioning
confidence: 82%
“…In addition to the techniques reviewed by Osborne et al (2001), O density can be inferred, with several assumptions and under geomagnetically quiet conditions, from incoherent scatter radar (ISR) data (Bauer et al, 1970;Hedin and Alcayde, 1974;Buonsanto et al, 1992;references in Vickers et al, 2013;Nicolls et al, 2014). Vickers et al (2013) found that high-latitude upper thermospheric density inferred from ISR was typically 10% to 25% larger than corresponding CHAMP observations, the differences being within the uncertainties of the measurements.…”
Section: Other Techniquesmentioning
confidence: 98%
“…Some results obtained from the CHAMP observations were summarized in the review paper presented by Lühr et al (2012). Vickers et al (2013) developed a new technique to obtain thermospheric neutral density at approximately 350 km altitude from incoherent scatter radar data. In situ comparisons with the CHAMP satellite show good agreement.…”
Section: Upper Thermospherementioning
confidence: 99%